Do the RMB exchange rate and global commodity prices have asymmetric or symmetric effects on China's stock prices? - Shaobo Long; Mengxue Zhang; Keaobo Li; Shuyu Wu (Financial Innovation, 2021)
With the rapid expansion of the RMB exchange rate's floating range, the effects of the RMB exchange rate and global commodity price changes on China's stock prices are likely to increase. This study uses both auto regressive distributed lag (ARDL) and nonlinear ARDL (NARDL) approaches to explore the symmetric and asymmetric effects of the RMB exchange rate and global commodity prices on China's stock prices. Our findings show that without considering the critical variable of global commodity prices, there is no cointegration relationship between the RMB exchange rate and China's stock prices, and the coefficient of the RMB exchange rate is not statistically significant. However, when we introduce global commodity prices into the NARDL model, the result shows that the RMB exchange rate has a negative effect on China's stock prices, that there indeed exists a long-run cointegration relationship among the RMB exchange rate, global commodity prices, and stock prices in the NARDL model, and that global commodity price changes have an asymmetric effect on China's stock prices in the long run. Specifically, China's stock prices are more sensitive to increases than decreases in global commodity prices. Thus, increases in global commodity prices cause China's stock prices to decline sharply. In contrast, the same magnitude of decline in global commodity prices induces a smaller increase in China's stock prices.
Keywords: F3; G1; 650; Asymmetric effects; China's stock prices; Global commodity prices; RMB exchange rate